KONSEP ISLAM DAN BUDAYA LOKAL (STUDI BUDAYA DAN SENI JAWA) - Deny Silvia (AL-ISHLAH: Jurnal Pendidikan, 2016)
Islam as a religion of rahmatan lil Alamin come to Indonesia cannot be separated from the shades where Islam was born. In Indonesia, Islam is able to adapt to the local culture. The process of integration of Islam in Indonesia is easily accepted by society. In the process of development, Islam is influenced by local culture, such as arts and culture or traditions in the past. For example, artwork of Grebeg Mulud, Gong sekaten bedug, sound art, carving, puppet, clothes piety and gamelan. The integration of Islam into the Javanese tradition is known by Islam Kejawen.